Vertical reduction of the learning content of the topic “Waste observation” of the discipline “Environmental monitoring - Shmatkov, D.; Shelkovyj, A.; Bielikova, N. (Problems of Engineer-Pedagogical Education, 2019)
After conducting a theoretical analysis of scientific, technical and methodological literature, studying and summarizing the experience of designing methods of didactic reduction, a method of vertical didactic reduction of the learning content of the environmental waste monitoring as an academic discipline has been developed using the methods of mathematical statistics. The method corresponds to the characteristic features of didactic reduction as it helps to transform the content into a certain form and coordinate it with the study time, and also ensures the formation of a certain amount of sufficient information to learn a specific aspect of the topic of the environmental waste monitoring. At the same time, the sufficiency of the content is substantiated, verified and confirmed using the methods of mathematical statistics, which made it possible to transform the qualitative variables “sufficiently” and “importantly” into quantitative variables. The implementation of the method leads to a decrease in time for measurements, calculations, and analysis when obtaining an approximate result with statistically small errors. It results in the maximization of information about the results obtained under conditions of limited study time, as well as under conditions of limited time for its implementation in future professional activities.